The Concept of Traditional Sports in Implementing the Independent Curriculum in Primary Schools: An Empirical Literature Study on Strengthening the Pancasila Student Profile - Simatupang, Hartono; Sari, Liliana Puspa; Usman, Khairul (Sekolah Tinggi Olahraga dan Kesehatan Bina Guna, 2025)
This study aims to develop an integrative concept of traditional sports as part of the implementation of the Independent Curriculum in primary schools through the framework of the Pancasila Student Profile Strengthening Project (P5). The research employs a qualitative descriptive method, using literature review as the main data collection technique, focusing on academic sources and documents related to the Independent Curriculum and Physical Education (PJOK). Data were analyzed through reflective and systematic processes to formulate an empirical understanding of how Pancasila values can be integrated into project-based learning through traditional sports. The findings reveal that the “Pancamain Indonesia” activity effectively supports the objectives of the P5 initiative through four main aspects: (1) establishing educational units as open ecosystems that encourage community participation, (2) providing space and opportunities for students to develop character and competencies, (3) designing project-based learning processes with clear and measurable outcomes, and (4) promoting interdisciplinary collaboration among teachers to enrich educational results. Hence, implementing traditional sports through Pancamain activities can serve as a strategic co-curricular approach to reinforce the Pancasila Student Profile within primary education.